Assessment of the effectiveness of health management information system training in Malawi: A case of Lilongwe District - Tambala, Jime Pandor (Kamuzu University of Health Sciences, 2022)
Health Management Information Systems remains the fundamental systems in the medical sector to support patients’ data and data for decision making. However, despite capacity rendered by different stakeholders to improve HMIS systems infrastructure, there exist data quality issues which affecting effective delivery of health care services in all districts of Malawi, Lilongwe included. As such, the study investigated the effectiveness of HMIS user Training in improving data quality in health systems in Malawi, a case of Lilongwe District. This was a cross-sectional study which used a mixed approach of both qualitative and quantitative methods, a total of 60 health workers participated in the study. In-depth interviews were conducted to analyze the perception of health workers towards HMIS training and to determine the factors that affect effectiveness of training of HMIS in Malawi. A semi-structured questionnaire was used to assess whether the structure and mode of delivery of HMIS training respond to the training needs. The study also measured quality of data by assessing four data dimensions; accuracy, completeness, timeliness and consistency. The study findings showed that good coordination in data management, data ownership, good documentation and team work were perceived as effects and benefits of HMIS training. While data verification, data analysis and use of electronic systems such as EMR and DHIS2 were perceived as skills acquired through HMIS trainings. Key data quality dimensions influenced by HMIS trainings were completeness, correctness while timeliness and consistency had some gaps which warrant for further investigations. According to this study HMIS training is clearly showing to be effective on HMIS performance. However further consideration should be given to how participants are selected, training duration, refresher trainings, staff retention, monitoring and supervision.